"Flâneur neurologique in paris" – A guide to pinpointing the houses of famous neurologists in the late XIX century. (June 2018) - Teive, Hélio Afonso Ghizoni; Germiniani, Francisco Manoel Branco; Camargo, Carlos Henrique Ferreira; Walusinski, Olivier; Lees, Andrew J.
Highlights: In the XIX, the Salpêtrière was the most important Neurology centre of the world. Charcot and pupils lived in the districts known as 7 éme and 8 éme arrondissements. Charcot had the habit of receiving guests from the medical, artistic and scientific areas. The development of Paris brought Charcot closer to his influencers and his students. Abstract: Introduction: During the last quarter of the XIX century, Paris, France, particularly the Salpêtrière Hospital was the most important centre of reference of Clinical Neurology in the world. The group based on the Salpêtrière Hospital, led by Professor Charcot, who was arguably the most celebrated neurologist in Europe. Objective: In this historical review, we present and locate the addresses of the houses of these famous Parisian neurologists from the late XIX century. Discussion: At that time, Charcot and the triumvirate of his most famous pupils, Pierre Marie, Joseph Babinski and Gilles de la Tourette, lived in different streets of Paris, predominantly in a small cluster in the districts known as 7 éme and 8 éme arrondissements (7th and 8th neighbourhoods). Professor Charcot lived in different streets and arrondissements of Paris, including the Rue du Faubourg Poissonnière, Paris IX; Cité de Trévise, Paris IX; Avenue du Coq, Paris IX; l'Hôtel de Chimay, Quai Malaquais Paris; and finally his most famous address at the Boulevard Saint-Germain, 217 (previously l'Hôtel de Varangeville), in the Faubourg Saint-Germain, Paris VII. (1884). Conclusion: The best urban organization in Paris provided an interaction between Charcot and other privileged minds of his day. We were remembering and visiting, as a " Flaneur Neurologique in Paris ", the addresses of the houses of these famous and outstanding Parisian neurologists from the late XIX century.